Decreased burden of revision hip replacements despite substantial rise in prevalence: a register-based analysis in Finland - Pamilo, Konsta J; Haapakoski, Jaason; Sokka-Isler, Tuulikki; Remes, Ville; Paloneva, Juha (Acta orthopaedica, 2022)
Background and purpose: While the incidence of THR operations has been established, little is known about the prevalence or the ratio of the annual number of revision THRs to the total number of THRs in the general population. By combining data from nationwide registers, we calculated the annual prevalence of THRs and the revision burden caused by THR survivors in Finland.Patients and methods: All primary THRs performed between 1980 and 2020 were identified from the Finnish Arthroplasty Register (FAR). Patient deaths were extracted from the Finnish Digital and Population Data Services Agency and THR revisions and removals from the FAR and the Finnish Hospital Discharge Register. We analyzed annual THR prevalence by dividing the number of THRs by the population aged 40 or older and the revision burden factor (RBF) by dividing the annual number of revisions by the total number of primary and revision THRs in the population. The proportions of bilateral implants and patients with THRs performed more than 10 years earlier (older THRs) were identified.Results: THR prevalence in Finland increased rapidly, reaching 3.6% in 2020. Between 2010 and 2020, the number of THRs increased by 50% and the prevalence of THRs by 38%. In 2020, the proportion of bilateral THRs had risen to 29% and the proportion of patients with older THRs to 36%. The RBF decreased between 1996 and 2020 from 3.1% to 1.3% (age- and sex-adjusted proportion ratio PR 0.42 [95%CI 0.39–0.45]).Interpretation: Despite the decrease in the RBF, the rapidly increasing prevalence of THRs potentially increases the number of revisits and revisions and thus poses a challenge for healthcare in the future.